Integration of Reading and New Literacies with Islamic Education - Maspul, Kurniawan Arif (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2024)
This review looks at how reading and new literacies are being integrated into Islamic education. It discusses the issues faced by educators and learners, assesses alternative approaches, and evaluates their compatibility with growing literacies and Islamic beliefs using case studies from